Post-decarbonisation and Generative Artificial Intelligence. Towards a possible methodology - Angelo Figliola; Maurizio Barberio (Techne, 2025)
The recent introduction of Generative Artificial Intelligence tools in architectural design has simultaneously opened new possibilities and raised questions about their appropriate use in holistic design processes, such as those related to environmental design. Avoiding the uncritical adoption of these tools is essential in a post-decarbonisation context, where the goal is to drastically reduce CO2 emissions and promote regenerative practices. Therefore, this paper proposes an operational methodology that integrates such tools within Sustainable-Aided Design, a holistic approach aimed at bridging the gap between architectural design and environmental design from the ultra-early stage of the design process.